APPLYING FIVE FORCES MODEL TO PHARMACEUTICAL INDUSTRY - Nedelcheva, Yulia; Filipova, Milena (Revista Inclusiones, 2020)
The aim of the article is to apply Porter’s model to pharmaceutical industry. The pharmaceutical industry is chosen as asubject of study due to its complexity and importance. The analysis has critic nature to the universality of the model. We take into account the opinion of other authors, as well as the dynamics of competitiveness analysis towards the new reality. The results of the article confirm the universality of the Porter’s model. The features of pharmaceutical industry are reflected in the model –the demand-side factors are leading over supply-side ones. In core of competitiveness assessment is customer’s satisfaction instead of ability to manufacturing of safe, effective and available pharmaceutical products.